Adubação silicatada na produção e qualidade de sementes e fibras de algodão (Gossypium hirsutum L.) - Gama, Juliana Simões Nobre (2014)
This research aimed to evaluate the effect of silicon on cotton, through variables agronomic, physiological, yield and fiber quality and seeds produced. The experiments were conducted in 2012 and 2013. In the first year of cultivation, were evaluated five levels of Si: 0, 1000, 2000, 3000 and 4000 kg Si ha-1, applied to soil, 0, 45, 60, 135 and 180 kg Si ha-1 foliar, and 0, 100, 200, 300 and 400 g kg seed-1, applied through seed coating. In the second year, were evaluated five levels: 0, 45, 60, 135 and 180 kg Si ha-1 and 0, 2000, 4000, 6000 and 8000 kg Si ha-1, applied via foliar and soil, respectively. The silicon source used is aluminum silicate. Evaluations were performed at 25, 50, 75 and 100 days from emergence (DAE). The results of the experiments allow to conclude that aluminum silicate applied by seed coating does not interfere in the physiological characteristics of cotton. However, when applied by foliar and soil, increases the chlorophyll index and reduces the diameter of the stem of cotton plants. In relation to yield, the number of seeds per fruit and number of fruit and seeds per plant were negatively affected with the increase of Si foliar applied. The silicon improves some physical characteristics of the fiber such as reflectance, short fiber index, degree of yellowing and micronaire index. Regarding the quality of seeds produced, increases the length of roots and shoots of seedlings, positively influences the weight of a thousand seeds by seed coating and soil and can increase productivity.